2015
DOI: 10.1109/tpami.2015.2420560
|View full text |Cite
|
Sign up to set email alerts
|

Gaussian-Based Hue Descriptors

Abstract: A robust and accurate hue descriptor that is useful in modeling human color perception and for computer vision applications is explored. The hue descriptor is based on the peak wavelength of a Gaussian-like function (called a wraparound Gaussian) and is shown to correlate as well as CIECAM02 hue to the hue designators of papers from the Munsell and Natural Color System color atlases and to the hue names found in Moroney's Color Thesaurus. The new hue descriptor is also shown to be significantly more stable und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The proposed lightness and chroma descriptors were shown to correlate as well as CIECAM02 descriptors to those of the corresponding Munsell designators, but have the additional advantage that they are more consistent across illuminants. Used in conjunction with the earlier Gaussian-based hue descriptor [2] they provide a foundation for the specification of the hue, lightness and chroma dimensions of object colours under average viewing surround conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The proposed lightness and chroma descriptors were shown to correlate as well as CIECAM02 descriptors to those of the corresponding Munsell designators, but have the additional advantage that they are more consistent across illuminants. Used in conjunction with the earlier Gaussian-based hue descriptor [2] they provide a foundation for the specification of the hue, lightness and chroma dimensions of object colours under average viewing surround conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The tests above have shown that the proposed KSM lightness and chroma descriptors correlate well with the Munsell value and chroma designators. Mirzaei et al [2][3] found that their Gaussian-based hue descriptor was more stable with respect to a change of illuminant than CIECAM02. This leads to the question as to whether the same will be true for KSM lightness and chroma.…”
Section: Robustness To Illuminant Changementioning
confidence: 99%
See 1 more Smart Citation
“…Two examples of such functions are plotted in Figure 1. The central-wavelength parameter, M, of KSM has been shown to be a very effective hue descriptor with hue defined as the peak wavelength, M, of the wraparound Gaussian function [6]. This hue descriptor correlates with the hue names found in Moroney's large, crowd-sourced Color Thesaurus [8].…”
Section: Ksm Wraparound Gaussian Reflectancesmentioning
confidence: 97%
“…This paper explores two features that lead naturally to definitions of focal colours [1] and colour categories. Colour categories are found by region segmentation of the set of possible colours defined in terms of wraparound Gaussian reflectances (Gaussian-like reflectances defined on the hue circle) as a function of central wavelength and sigma in KSM (𝑘𝜎𝜇) coordinates [6] (details below). Focal colour as the representative of a colour category is defined in terms of its tolerance to different illuminants without any chromatic adaptation.…”
Section: Introductionmentioning
confidence: 99%